Preservation and utilization dialogue in Indonesia’s future capital city - Lambang Subagiyo; Nurul Fitriyah Sulaeman; Atin Nuryadin (Institute of Advanced Engineering and Science, 2026)
Environmental sustainability has become crucial, especially in tropical environments that act as lungs for the world. Therefore, exploring the pro-environmental behavior (PEB) of young citizens of Eastern Borneo in Indonesia is beneficial. Exploration focused on the PEB category of students, the PEB aspect (preservation, utilization, appreciation), and student responses to the local environmental issues. This study surveyed 651 9th-grade students (15-year-olds) in six cities around Eastern Borneo. The measurement of PEB was carried out using the adapted two major environmental values model with an added scale for appreciation. Additional open-ended questions were applied to clarify the students’ perspectives on the significant environmental issues in Eastern Borneo. The result showed that only half of the students (51.31%) had advanced PEB, with the rest classified as transitional (48.23%) and naive (0.46%). Among the three PEB aspects, utilization scored the highest, indicating that the students were strongly inclined to endorse the importance of environmental utilization for human welfare. Moreover, the majority favored relocating the capital city, which highlights the importance of a new capital city owing to the overcrowded state of the current capital city (Jakarta) and the decentralization of the development of Indonesia. Nevertheless, it was found that they are concerned about preservation and sustainability regarding coal mining and palm plantations. Therefore, it was considered that environmental education for students needs enhancement to shape their PEB with contextual environmental issues.